Liars' room - Poblocki, Dan (Scholastic Press, 2021)
"Simon is a liar. Stella and Alex know this about their new stepbrother, so they aren't bothered by his stories about their new house. But Simon is getting harder and harder to ignore, as his cries for attention become increasingly dangerous and difficult to explain."--